(untitled) (African Journal of Biomedical Research, 2020)
Respiratory conditions are among the causes of morbidity and mortality in children with Cerebral Palsy (CP). Little attention is given to how respiratory symptoms could affect quality of life (QOL) of these children. This study examined relationship between respiratory symptoms and QOL of children with CP. A total of 95 children participated in this cross-sectional study. Respiratory symptoms and QOL were assessed using Respiratory Symptom Questionnaire and Paediatric QOL Questionnaires respectively. Data obtained were analysed with Spearman Rank Order Correlation and Chi-square analyses to find relationship between respiratory symptoms and QOL and the association between respiratory symptoms and different types of CP respectively. All statistics were performed using SPSS version 20 at 0.05α significance level. There were 57 (60%) male and 38 (40%) female participants with mean age of 2.76 ±2.0years. Fifty-six (55.8%) of the children have spastic hemiplegia, 32 (31.6%) spastic quadriplegia and 13 (12.6%) spastic diplegia. The common respiratory symptoms were phlegm production 44(46.3%), cough 38(40%), dyspnoea 22(23.2%) and wheezes 21(22.1%). Significant negative correlation was observed between cough and QOL (r=-0.234, p=0.022). Phlegm production was significantly associated with quadriplegic type of CP (p<0.05). Respiratory symptoms are common among children with CP and they could deteriorate the children’s QOL. Pulmonary physiotherapy should be incorporated into the routine rehabilitation of these children.